Prognostic value of metabolic tumor burden in lung cancer - Obara, Piotr; Pu, Yonglin (Chinese Journal of Cancer Research, 2013)
Accurate prognosis in patients with lung cancer is important for clinical decision making and treatment selection. The TNM staging system is currently the main method for establishing prognosis. Using this system, patients are grouped into one of four stages based on primary tumor extent, nodal disease, and distant metastases. However, each stage represents a range of disease extent and may not on its own be the best reflection of individual patient prognosis. 18F-fluorodeoxyglucose-positron emission tomography (18F-FDG-PET) can be used to evaluate the metabolic tumor burden affecting the whole body with measures such as metabolic tumor volume (MTV) and total lesion glycolysis (TLG). MTV and TLG have been shown to be significant prognostic factors in patients with lung cancer, independent of TNM stage. These metabolic tumor burden measures have the potential to make lung cancer staging and prognostication more accurate and quantitative, with the goal of optimizing treatment choices and outcome predictions.